Analisis Manajemen Pendidikan di SMA 63 Jakarta - Putri Shabilla Achmad; Ade Nurqodrillah; Matnur Ritonga (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
This study aims to describe the management in an educational institution, especially at SMA Negeri 63 Jakarta. This study uses a qualitative approach with descriptive analysis methods namely, describing, explaining, and disclosing the results of education management research that apply to secondary education at the national level at SMAN 63 Jakarta so that this research can be clearly described. The results of this study are that management has an important role in all components of education, so that the stakeholders try to optimize all components of education in accordance with the educational standards set in Indonesia. Starting from the curriculum, educational staff, students, teachers, financing, administration, public relations and facilities and infrastructure, all efforts are made to be able to uphold success in achieving educational goals effectively and efficiently through proper management or supervision. Even though there are several obstacles in its application, both teachers and students need to adapt to the education system which changes and continues to grow.